DEVELOPMENT OF QR CODE BASED POP UP BOOK ON EARLY MARRIAGE MATERIAL FOR EARLY ADOLESCENTS - Farah Nabila Nur Afifah, (Jurnal Teknologi Pendidikan, 2024)
This study aims to: (a) Describe the systematic steps of developing QR code-based pop up book learning media on early marriage material; (b) Know the feasibility of QR code-based pop up book learning media on early marriage material by experts; (c) Know the practicality of QR code-based pop up book learning media on early marriage material by users. This research is a development or R&D research using the ADDIE model. The media is declared feasible based on validation with media experts and material experts. Media expert validation received a final score of 5 which was included in the very feasible category so it was declared feasible to be tested without revision. Material expert validation received a final score of 5 which was included in the very feasible category so it was declared feasible to be tested without revision. The media was declared practical by the results of students' responses in the field trial which obtained an average of 4.27 with the category “very practical” and the teacher's response in the field trial obtained an average of 4.55 with the category “very practical”.